Motivational Interviewing for Hearing Aid Use: A Systematic Meta-Analysis on Its Potential for Adult Patients with Hearing Loss - Liu, Alice Q.; Wu, Bella; Nunez, Desmond A. (Journal of the American Academy of Audiology, 2021)
Purpose The aim of the study is to conduct a meta-analysis examining the impact of motivational interviewing (MI) on hearing aid (HA) use compared with standard care.Research Design The research design is a systematic review and meta-analysis. Cochrane ENT, Central, Medline, Web of Science, ICTRP, and ClinicalTrials.gov electronic databases were searched. Inclusion criteria consisted of randomized controlled trials (RCTs) published between 1988 and 2018 that compared MI to standard care.Study Sample The study sample consists of four RCTs, investigating a total of 176 patients.Data Collection and Analysis RevMan 5.3 and a random effect model were used for analysis.Results The standardized mean difference in data-logged hours of HA use was not statistically significant (0.34 [95% confidence interval or CI: −0.10, 0.78; p = 0.13]). The mean difference for user-reported outcomes on the International Outcome Inventory—Hearing Aids of 0.41 [CI: −1.00, 1.82; p = 0.57] was also not significant.Conclusion There is no current evidence that MI significantly improves HA use or user-reported outcomes. However, there were limited studies included in this review and further research is indicated.
Keywords: motivational interviewing; hearing aid; amplification